Everyday health security practices as disaster resilience in rural Bangladesh. Issue 2 (17th February 2016) - Ray-Bennett, Nibedita S.; Collins, Andrew E.; Edgeworth, Ross; Bhuiya, Abbas; Nahar, Papreen; Alamgir, Fariba
ABSTRACT: Health security is a relatively new concept in terms of how it is practised in disaster-prone locales. We observed 10 rural households in Bangladesh for four months using informal interviews, field diaries, and observation. The findings suggest that the everyday practises of health security involve the capabilities of "caring for themselves" in resource-constrained contexts. Understanding how households care for themselves prior to and during disasters presents an opportunity to examine how improved health might reduce the effects of disasters, ill health, and poverty. Some interventions are proposed to improve health security for poorer households in general and women in particular.